Improving the level of food security of the region: cluster approach - M. V. Andreeva; O. B. Kirik; A. S. Borisova (Вестник университета, 2021)
Scientific approaches to the study of food security at the regional level of the Russian Federation are considered. The main indicators characterizing the level of food security of the Vologda region have been analysed. The main problems in providing the population of the region with food products of their own production have been identified. The problem of the low level of production of meat and meat products in the region has been identified as a problem that requires the most careful attention of regional government bodies. It has been concluded that the strengthen state support for meat livestock enterprises of the region is necessary. The analysis of the opinions of domestic scientists on the application of the cluster approach to the development of the agro-industrial complex has been carried out. The expediency of creating a meat cluster of the Vologda region as a promising tool for solving the problem of the low level of provision of the population of the region with meat is justified. The results of the SWOT analysis of the meat cluster of the Vologda region have been presented. The general concept of the meat cluster of the region is proposed.